Indigenous entrepreneurship: Entrepeneurial intentions of Dayak youth in Sarawak, Malaysia - Ollince, anak Tateh (Universiti Malaysia Sarawak (UNIMAS), 2013)
ThiS study involves two aspects that have major influence to entrepreneurship as commonly described in literature: the personality traits and social variables. The interest of study was on Dayak group in Sarawak, comprises of Iban, Bidayuh and Orang Ulu (Bisayah, Kayan, Kenyah, Kelabit and Berawan The present study finds that, despite increasing attention on indigenous entrepreneurship, there remains a lack of multidimensional research on entrepreneurial intentions of non-Malay indigenous communities in Malaysia. With the use of quantitative methods for data collection and analysis, the impacts of personality traits and social variables of the respondents on development of their entrepreneurial intentions were investigated The findings showed that the respondents' entrepreneurial intentions could be predicted using both their personality traits (innovativeness) and social variables (knowledge and experience, family upbringing).